Edukasi Dampak dan Solusi Pernikaham Usia Dini Pada Siswa SMP Negeri 7 Penukal Desa Air Itam Timur Kabupaten Penukal Abab Lematang Ilir (PALI) tahun 2025 - Ratna Dewi; Trio Utomo; Nadia Septiani; Rara Febriana; Agnes Tirani; Sinta Afriani; Siti Kamaria; Dalina Dalina; Fitriyanti Fitriyanti; Dia afsari (JURNAL PENGABDIAN KADER BANGSA, 2026)
Early marriage is not a new thing in Indonesia. Early marriage is a phenomenon that is considered normal in the general public. Cases of early marriage are social problems that occur in adolescents, the most victims of early marriage are adolescent girls and occur more in rural areas than in urban areas, early marriage often occurs in poor families, and those with low education. Early marriage is a marriage carriedout by couples before the age of The percentage of the population in PALI district who married at a young age from 2020-2022 was 50% of the population who married at ayoung age, most of whom were women. The purpose of this service is to increase the knowledge of students of SMP N7 Penukal, Air Itam Timur Village, PALI Regency about the impacts and solutions to early marriage. The steps of the activity consist of establishing cooperativerelationships, submitting proposals and setting schedules, and involving process evaluations with question and answer sessions. This counseling involves lecture methods, discussions and questions and answers, audio-visual media. The results of this community service activity are that there is an increase in understanding and knowledge of students of SMP N7 Penukal, Air Itam Timur Village, PALI Regency about the negative impacts and dangers of early marriage and efforts to prevent early marriage. Suggestion There needs to be cooperation from variousparties to prevent early marriages that have negative impacts and continue to make efforts to socialize education on the dangers of early marriage for teenagers.